Prostitution as a Form of Self-Destructive Behavior - S.V. Gorbatov; E.N. Arbuzova (Психология и право)
The article presents the results of a theoretical analysis and comparative study of prostituted women in the context of the study of prostitution as a phenomenon of self-destruction. The results of an empirical study are presented, including the peculiarities of experiencing bodily experience and the psychosocial organization of respondents with different forms of self-destructive behavior. A total of 526 women aged 18 to 41 years (M=25.3 years) participated in the study. Including: those involved in prostitution (N=44); with experience of self-harm (N=198); diagnosed with an eating disorder (N=82) and control sample respondents (N=202). The results of theoretical and empirical research allow us to conclude that prostituted women can be classified as persons prone to self-destruction. The study revealed in them markers of autoaggression towards their bodies, the thinness of psychological boundaries, deprivation of psychological space and diffuse ego identity.